Transport and accumulation of floating marine litter in the Black Sea: insights from numerical modeling - Castro-Rosero, Leidy M.; Hernandez, Ivan; Alsina, José M.; Espino, Manuel (Frontiers in Marine Science, 2023)
Floating marine litter (FML) is a global problem due to the risk it poses to marine life and human health. In a semi-enclosed basin such as the Black Sea, the slow replenishment of water and the strong input from European rivers potentially favor the increasing accumulation of FML.This study presents the validation and use of an FML dispersion and accumulation numerical model, assesses the contribution of Stokes drift and the accumulation patterns of marine litter in the Black Sea. Moreover, the study discusses the importance of considering Stokes drift in a numerical model for the transport of FML in the Black Sea from the main river discharge points. Three scenarios were conducted, two with homogeneous particle release including and excluding the Stokes drift, and the third with a particle release from the nine main river basins. In all scenarios, the southwest coast was identified as having a high density of FML. The mainly cyclonic circulation, the large input of FML from the Danube River and other northern rivers, including a relevant fraction of the outflow from the Kerch Strait, likely explain this. The inclusion of Stokes drift strongly influenced the residence time of particles in offshore waters and the percentage of particles that washed up on the shore. The percentage of particles beached on the shore increased from 45.5% to 75.5%, and the average residence time decreased from 99 to 63 days when Stokes drift was considered. These values are in agreement with recent literature that supports an overestimation of residence times by omitting Stokes drift. In comparison to previous modeling studies, the eastern region in the vicinity of the Georgian coast and the northwestern Black Sea region were identified as high-density areas, supported by observational data.